The Impact of Learning Motivation and Learning Activeness for the Result of Social Subject in SMP Negeri 7 Pematang Siantar - Erika Hutapea; Injen Pardamean Butar-Butar; Herlina Hotmadia Sianipar (MultiTech Publisher, 2023)
This research aims to obtain knowledge regarding the influence of student learning motivation and learning activeness on student learning outcomes in social studies subjects for class VIII students at SMP Negeri Pematang Siantar. This type of research is quantitative research with a quantitative descriptive data analysis approach with the testing media used is Microsoft Excel . The total population in this study was 146 students. The sample collection technique used was the Slovin formula. The data collection technique used was a questionnaire. Hypothesis data collection techniques use simple regression analysis, multiple regression analysis and coefficient of determination (R2). The results of this study state that: 1) There is a positive and significant influence of learning motivation on learning outcomes , this result can be seen in the t test where the calculated t value of learning motivation ( 0.02 ) > t table value (1.690 ) which means that this variable is significant. 2) There is a positiv and significant influence on student learning activity on learning outcomes. This result can be seen in the t test where the calculated t value of student learning activity ( 3.66 > t table value ( 0.334 ) which means this variable is significant. 3 ) Learning motivation and student learning activity together influence learning outcomes, this result can be seen in the F test where the calculated F value ( 1140.14 ) > table F value ( 0.334 ). The R Square coefficient of determination test was found to be 0.971, which means that 97.1% of the variables of student motivation and active learning have an influence on student learning outcomes at the SM P Negeri 7 Pematang Siantar school, and the remaining 2.9% is the influence of variables that were not studied. in this research .